2012
DOI: 10.1016/j.earlhumdev.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Children born small for gestational age are not at special risk for preschool emotion and behaviour problems

Abstract: Despite the wealth of literature examining long term outcomes of preterm low birthweight children, few studies have directly assessed the developmental impact of being born full term but small for gestational age (SGA). We aim to determine whether (i) being SGA increases preschool behavioural problems and (ii) other risk factors operate differently in SGA and appropriate for gestational age (AGA) controls. 550 New Zealand European mothers and their 3.5 year old children participated in this study. All children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 64 publications
1
9
0
1
Order By: Relevance
“…Emotional problems were prevalent in the SGA group, supporting the results of Berle et al [41] who found increased risk of anxiety and depressive symptoms in term-born SGA adults. Emotional and behavioral problems were however not seen by Cornforth et al [42] in preschool children, possibly indicating that other aspects, such as genetics or environmental factors, are influential for adult psychiatric symptoms in this group, or perhaps an age specific expression of problems. Almost one in four had borderline/clinical level of Somatic Complaints in the SGA group, and a higher level of self-reported pain compared to normal birthweight peers has been reported [43].…”
Section: Discussionmentioning
confidence: 63%
“…Emotional problems were prevalent in the SGA group, supporting the results of Berle et al [41] who found increased risk of anxiety and depressive symptoms in term-born SGA adults. Emotional and behavioral problems were however not seen by Cornforth et al [42] in preschool children, possibly indicating that other aspects, such as genetics or environmental factors, are influential for adult psychiatric symptoms in this group, or perhaps an age specific expression of problems. Almost one in four had borderline/clinical level of Somatic Complaints in the SGA group, and a higher level of self-reported pain compared to normal birthweight peers has been reported [43].…”
Section: Discussionmentioning
confidence: 63%
“…Although previously published papers from our sample have reported no significant difference in outcome between SGA and AGA children, SGA status was adjusted for in the analysis (22). If univariable analyses were statistically significant at the 10% level or below, then these outcomes were analysed in multivariable models by adding SGA status, sex, maternal school leaving age, method of delivery, maternal smoking in pregnancy and duration of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…If univariable analyses were statistically significant at the 10% level or below, then these outcomes were analysed in multivariable models by adding SGA status, sex, maternal school leaving age, method of delivery, maternal smoking in pregnancy and duration of breastfeeding. Although previously published papers from our sample have reported no significant difference in outcome between SGA and AGA children, SGA status was adjusted for in the analysis (22). Results were considered significant if the p-value was less than 5% in the Ethics Each phase of the study received ethical approval from the Auckland Regional Ethics Committee.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to previous work, lower birth weight centile was not independently associated with increased ADHD symptom severity in our data set. In general, literature demonstrates there is an association between restricted fetal growth and ADHD symptom severity [Bhutta et al, 2002;Indredavik et al, 2004;Lahti et al, 2006], however, null findings have also been reported [Cornforth et al, 2012]. In this sample largely consisting of ADHD cases, levels of inattention and hyperactivity-impulsivity were elevated and represented the upper end of the ADHD risk spectrum.…”
Section: Discussionmentioning
confidence: 70%
“…The strength of this association, however, varies across studies [Nigg, 2006] and is not always replicated [Cornforth et al, 2012]. Consistent with the dimensional nature of ADHD [Levy et al, 1997;Coghill and Sonuga-Barke, 2012], the association between lower birth weight and ADHD-related phenotypes is continuous and extends into the normal birth weight range [Boulet et al, 2009;Phua et al, 2012;Qiu et al, 2012;Walhovd et al, 2012].…”
Section: Introductionmentioning
confidence: 94%